Century scale rainfall in the absolute Atacama Desert: Landscape response and implications for past and future rainfall. (15th February 2021) - Pfeiffer, Marco; Morgan, Alexander; Heimsath, Arjun; Jordan, Teresa; Howard, Alan; Amundson, Ronald
Abstract: The Atacama Desert contains the driest regions on Earth, with significant rain occurring only a few times per century, based on sparse historical records. However, the frequency and magnitude of rainfall remains speculative. On March 24–26 of 2015, an unusual storm caused rainfall rates and quantities to exceed many historical records. Of interest is whether this storm was able to activate geomorphic processes whose impacts are evident on numerous landscape features. Here, the results of a reconnaissance from N to S transecting through the plant-free expanse of the Atacama Desert, between 22 and 26° S, are examined in relation to evidence of past runoff activity coupled with soil architecture and soil hydraulic properties. The results suggest the rain initiated some minor runoff processes on the upper hillslopes. However, the rainfall was too small to reactivate many features that appear to be driven by larger, less frequent storms. The field evidence suggests that larger scale rainfalls have occurred throughout the Quaternary, and that there are fossilized (or infrequently active) features in various stages of "repair" that provide evidence of rainfall re-occurrence. The landscapes largely escaped overland flow alteration due to the high infiltration rate capacity caused by the salt-rich soils, which we estimated to average 78 mm h −1 for hillslopes and 244 mm h −1 for alluvial soils, based on disc infiltrometer measurements. This gives a resilience, and potential rainfall threshold, to alteration by intensive rainfall events. Published paleoclimatic records coupled with evidence from soil examined at the arid/hyperarid periphery of the desert show evidence of a cessation of carbonate formation since ∼11 ka, a time of aridification similar to the drying of lakes and marshlands in the hyperarid region. Thus, the past fluvial alteration features are likely to be, at least partially, remnant Pleistocene features which have been largely unaffected by Holocene events, whose magnitudes were similar to that of 2015. Highlights: On March 2015 an unusual storm caused rainfall rates and quantities to exceed many historical records in the Atacama Desert. Rainstorm seemed to be sparsely affected at the driest area of the desert. Evidence suggests that the soil has an important influence on the landscape's response to rainfall in the Atacama Desert. The absolute Atacama Desert has a resiliency to impact from rainfall due to high rates of water infiltration into soil.